THE ROLE OF CORONARY ARTERY PLAQUE IN PREDICTION OF CORONARY ARTERY DISEEASE USING PHARMACOLOGICAL-STRESS ECHOCARDIOGRAPHY - Andova, Valentina; Zafirovska, Planinka; Srbinovska-Kostovska, Elizabeta; Georgievska-Ismail, Ljubica (Journal of Morphological Sciences, 2020)
It was confirmed that coronary artery plaque [CAP] and its larger burden may influence myocardial perfusion independent of presence of significant coronary artery stenosis.The aim of our study was to examine the role of CAP as predictor of coronary artery disease [CAD] presence  using pharmacological stress echocardiography [SE]. We prospectively assessed 61 consecutive patients with symptoms implying CAD who underwent dipyridamole or dobutamine SE and coronary angiography. Conventional 2D echocardiographic wall motion score index [WMSI] as well as global LV longitudinal strain using speckle tracking [GLS%] were measured at rest and peak stress. Out of 61 patients, 25/41.0% had normal coronary arteries, 18/29.5% had obstructive CAD and 18/29.5% had nonobstructive CAD with CAP. In patients with CAP, GLS% at maximal SE showed worsening in comparison to those with and without CAD who showed insignificant lower GLS% or better function after SE [p=0.057]. Presence of CAP [OR=8.358; 95%CI 1.929-36.216;p=0.005] and worsening of WMSI at maximal SE [OR=190.5; 95%CI 2.517-14426.687;p=0.017] appeared as independent predictors of CAD presence, while worse values of GLS% at maximal SE [OR=1.155; 95%CI 0.999-1.334;p=0.051] as well change [increase] of the number of segments with LS< 12% at maximal SE [OR=0.755; 95%CI 0.602-0.946;p=0.015] appeared as independent predictors of CAP presence. Coronary artery plaque presence appeared as independent predictor of CAD as well as worse values of GLS% Key words : coronary artery plaque, coronary artery disease, stress echocardiography, LV systolic longitudinal strai